THE POLITICAL CONTEXT OF THE DEVELOPMENT OF TRADITIONAL KYRGYZ MEDICINE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines in detail some of the traditional medicine practices found in the Manas epic, a remarkable monument of Kyrgyz traditional culture. The valuable information on traditional medicine contained in the epic is analyzed. Before the development of medical science, traditional healing methods and their unique features were studied among the Kyrgyz people. This article defines the categories of Kyrgyz traditional medicine methods, as well as “cold” and “hot” treatments. It also provides a detailed description of the healers who used these treatments, as well as their distinctive methods and techniques. The names, properties, and treatment methods of medicinal herbs, decoctions, and infusions mentioned in the Manas epic poem are presented. The place and significance of these herbs among the local population are described in detail, as are the treatment methods used by Kyrgyz healers for various ailments. This article examines the development of scientific medicine in Kyrgyzstan in the pre-Soviet period, including the opening of medical centers and later hospitals for Russian peasant settlers.